Design, Modeling and Simulation of a High-Pressure Gasoline Direct Injection (GDI) Pump for Small Engine Applications / Amin Mahmoudzadeh Andwari ... [et al.] - Andwari, Amin Mahmoudzadeh; Muhamad Said, Mohd Farid; Abdul Aziz, Azhar; Esfahanian, Vahid; Zadeh, Ali Salavati; Idris, Mohamad Asmawi; Mohd Perang, Mohd Rozi; Mohd Jamil, Hishammudin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In this study, a plunger-type high-pressure fuel pump is designed for use in a Gasoline Direct Injection (GDI) system and intended to retrofit onto small spark ignition (SI) engines of less than 0.2 liter/cylinder. The pump is developed to generate high-pressurized fuel in range of 4-20 MPa, and is capable of supplying fuel transfer of 10-20 g/s. SolidWorksTM software was extensively used in the analysis to design the pump via 3D modeling approach. The designed model was then analyzed using ANSYS FluentTM software to simulate for the flow pattern as well as the pressure distribution in the pump cavity during pumping process. The concept, design geometry, calculation and the testing method employed for the high-pressure fuel pump are discussed in this paper. This research aims to design a high-pressure fuel pump used in small spark ignition engines applications wherein to improve the efficiency of the engine, the fuel pump is driven by an external DC motor, relieving the engine in providing the auxiliary power supply. In general based on the simulation, during pumping process at 1000 RPM (using the two cam lobe design), the pump is able to supply fuel at 6.00 MPa of the discharge pressure. The fuel was able to be delivered by as much as 0.0196 kg/s, at a travelling velocity of 3.8 m/s, in which this is well in the range of the initial pump design requirements.